KAJIAN PERILAKU GENERASI Z TERHADAP PEMILIHAN APLIKASI PENGINGAT WAKTU SALAT DENGAN PENDEKATAN THEORY OF PLANNED BEHAVIOR - Lestari, Suci Ayu; Amir, Rahma (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract This study aims to analyze the behavior of Generation Z in choosing prayer time schedule applications based on the Theory of Planned Behavior (TPB), focusing on the influence of attitudes, subjective norms, and perceived behavioral control on usage intentions, as well as how usage frequency strengthens these intentions. A quantitative method with a survey design was employed. Data were collected through questionnaires distributed to 100 Generation Z respondents in Makassar City using purposive sampling techniques. The instrument was tested for validity and reliability, then analyzed using descriptive statistics and multiple linear regression. The results show that: 1) Attitudes, subjective norms, and perceived behavioral control simultaneously have a significant effect on Generation Z's intentions to choose prayer time schedule applications (F=0.000; R²=54.1%). Partially, subjective norms (p=0.000) and perceived behavioral control (p=0.000) have significant effects, while attitudes (p=0.923) do not. The most widely used applications are Al-Qur'an Indonesia (45%) and Muslim Pro (42%) because they are considered easy to use, have complete features, and attractive displays. 2) The frequency of application use plays a role in strengthening intentions; the more frequently the application is used (42% of respondents open it 2-3 times/week), the more habits and trust are formed, reinforcing positive attitudes and perceived behavioral control, thereby increasing the intention to continue using the application. This study confirms that TPB can explain Generation Z's intentions in choosing religious applications and recommends that application developers enhance ease of use and attractive features. Keywords: Generation Z, Prayer Time Schedule Application, Theory of Planned Behavior, Usage Intention